Human Rights in Islam: Compatible and Incompatible Aspects - Ahmad, Muneeb (International Journal of Psychosocial Rehabilitation, 2020)
his scholarly research article delves into the intricate interplay between Islam and human rights, meticulously dissecting both compatible and incompatible aspects within the context of Islamic teachings. Employing a comprehensive analysis of Qur’anic verses, Hadith, scholarly interpretations, and historical contexts, this study elucidates the nuanced relationship between Islamic principles and universal human rights standards. It explores the foundational tenets of human dignity, equality, justice, and freedom within Islam, while critically examining challenges arising from diverse interpretations and cultural practices. Through this exploration, the research aims to foster a deeper understanding of the complexities surrounding human rights in Islam, promoting dialogue and mutual respect between different cultural and religious perspectives.